2023
DOI: 10.1083/jcb.202110162
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast single-molecule imaging reveals focal adhesion nano-architecture and molecular dynamics

Abstract: Using our newly developed ultrafast camera described in the companion paper, we reduced the data acquisition periods required for photoactivation/photoconversion localization microscopy (PALM, using mEos3.2) and direct stochastic reconstruction microscopy (dSTORM, using HMSiR) by a factor of ≈30 compared with standard methods, for much greater view-fields, with localization precisions of 29 and 19 nm, respectively, thus opening up previously inaccessible spatiotemporal scales to cell biology research. Simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 83 publications
4
14
0
Order By: Relevance
“…S3). These also revealed the presence of clustered regions within focal adhesions similar to previous studies [46,[49][50][51][52].…”
Section: Nanoclusters Of Phosphorylated Focal Adhesion Proteins Are O...supporting
confidence: 89%
See 1 more Smart Citation
“…S3). These also revealed the presence of clustered regions within focal adhesions similar to previous studies [46,[49][50][51][52].…”
Section: Nanoclusters Of Phosphorylated Focal Adhesion Proteins Are O...supporting
confidence: 89%
“…1g) [31,48]. Taken together our results revealed that adhesions were composites of persistent regions with dense integrin β3 nanoclusters, as well as short-lived fast exchanging regions [31,32,46,48]. Since activation of integrins promotes their immobilization, which is further stabilized by their connections to ECM and actin-binding proteins [31,32], organisation of integrins into these long-lived immobile regions could provide a high spatial and temporal stability, which could function as robust platforms to organise signalling hubs of downstream signalling proteins within the focal adhesions.…”
Section: Resultssupporting
confidence: 62%
“…hierarchical fashion inside FAs, forming nanoclusters similar to the ones reported here, that further enrich into compartmentalized regions around 300 nm in size (39). To enquire whether such hierarchical organization is present in our data, we performed nearest-neighbor distance (NND) analysis between nanoclusters of the same proteins (Fig.…”
Section: It Has Been Recently Proposed That Adhesion Proteins Includi...supporting
confidence: 57%
“…Considering the canonical view that integrins inside FAs are bound to paxillin and engaged to talin and vinculin (45,47), these results might be surprising at first sight, as one would expect a much higher fraction of EED-NN values below zero. Nevertheless, using super-resolution microscopy, others have also found negligible spatial colocalization of integrins with these adaptor proteins (38,39).…”
Section: Global Mesoscale Organization Of Adhesion Protein Nanocluste...mentioning
confidence: 99%
See 1 more Smart Citation